Інституційне забезпечення розширення функціоналу регіональних наукових центрів нан україни та мон україни у контексті смарт-спеціалізації (на прикладі Придніпровського економічного району) - Підоричева, І.Ю. (Вісник економічної науки України, 2020)
Підписанням Угоди про асоціацію між Україною та ЄС, внесенням змін до Конституції України щодо реалізації стратегічного курсу на набуття повноправного членства в ЄС, затвердженням Стратегії національної безпеки України, у якій магістральним напрямом розвитку української держави визнано європейську інтеграцію, Україна здійснила свій цивілізаційний вибір. Реалізація цього цивілізаційного вибору зобов’язує Україну йти шляхом імплементації євроінтеграційних реформ, переймати правила, норми і практики ЄС для успішної інтеграції в європейський простір і систему формальних інститутів ЄС. Це, у тому числі стосується необхідності врахування європейського підходу до територіального поділу та регіональної політики, впровадження підходу смарт-спеціалізації у систему стратегічного планування регіонального розвитку. Розбудова регіональних інноваційних екосистем, налагодження ефективних взаємозв’язків між усіма їх акторами відіграє вирішальну роль в успішній реалізації регіональних стратегій смарт-спеціалізації.
Проаналізовано систему взаємозв’язків між акторами регіональної інноваційної екосистеми Придніпровського економічного району на предмет їх наявності та інтенсивності порівняно з іншими регіонами та Україною в цілому. Визначено, що як національній, так і регіональним інноваційним екосистемам України (у тому числі Придніпровського економічного району) бракує ефективних взаємозв’язків між їх ключовими акторами.
Обґрунтовано науково-інституційні положення та рекомендації щодо формування регіональних інноваційних екосистем на рівні економічних районів України, які відповідають вимогам європейської класифікації NUTS 1, в умовах імплементації Угоди про асоціації та підходу смарт-спеціалізації, що полягають в обґрунтуванні наділення регіональних наукових центрів НАН України та МОН України додатковими повноваженнями з координації зв’язків між акторами регіональних інноваційних екосистем в межах ареалів їх дії та у внесенні змін і доповнень до Закону України «Про наукову і науково-технічну діяльність» щодо розширення функцій і повноважень регіональних наукових центрів, перетворення їх у ефективно діючі міжрегіональні координаційні центри інноваційного розвитку.
Запропоновано підхід до формування Подільської регіональної інноваційної екосистеми в межах Подільського економічного району. На базі Придніпровського наукового центру НАН України та МОН України запропоновано реалізувати ряд експериментів, по-перше, з формування Придніпровської регіональної інноваційної екосистеми; по-друге, за участю експертної спільноти створити міжрегіональну громадську спілку «Платформа інноваційного розвитку «Придніпров’я»», яка може стати «фабрикою думки» щодо шляхів і засобів перезавантаження відносин між акторами регіональної інноваційної екосистеми та неоіндустріального відродження Придніпров’я. Подписанием Соглашения об ассоциации между Украиной и ЕС, внесением изменений в Конституцию Украины относительно реализации стратегического курса на обретение полноправного членства в ЕС, утверждением Стратегии национальной безопасности Украины, в которой магистральным направлением развития украинского государства признано европейскую интеграцию, Украина осуществила свой цивилизационный выбор. Реализация данного цивилизационного выбора обязывает Украину идти путем имплементации евроинтеграционных реформ, перенимать правила, нормы и практики ЕС для успешной интеграции в европейское пространство и систему формальных институтов ЕС. Это, в том числе касается необходимости имплементации европейского подхода к территориальному делению и региональной политики, внедрения подхода смарт-специализации в систему стратегического планирования регионального развития. Развитие региональных инновационных экосистем, налаживание эффективных взаимосвязей между их ключевыми акторами играет решающую роль в успешной реализации региональных стратегий смарт-специализации.
Проанализирована система взаимосвязей между акторами региональной инновационной экосистемы Приднепровского экономического района на предмет их наличия и интенсивности по сравнению с другими регионами и Украиной в целом. Определено, что как национальной, так и региональным инновационным экосистемам Украины (в том числе Приднепровского экономического района) не хватает эффективных взаимосвязей между ключевыми акторами.
Обоснованы научно-институциональные положения и рекомендации по формированию региональных инновационных экосистем на уровне экономических районов Украины, которые отвечают требованиям европейской классификации NUTS 1, в условиях имплементации Соглашения об ассоциации и подхода смарт-специализации, состоящие в обосновании наделения региональных научных центров НАН Украины и МОН Украины дополнительными полномочиями по координации связей между акторами региональных инновационных экосистем в пределах ареалов их действия, а также внесении изменений и дополнений в Закон Украины «О научной и научно-технической деятельности» по расширению функций и полномочий региональных научных центров, превращению их в эффективно действующие межрегиональные координационные центры инновационного развития.
Предложен подход к формированию Подольской региональной инновационной экосистемы в пределах Подольского экономического района. На базе Приднепровского научного центра НАН Украины и МОН Украины предложено реализовать ряд экспериментов, во-первых, по формированию Приднепровской региональной инновационной экосистемы; во-вторых, с участием экспертного сообщества создать межрегиональный общественный союз «Платформа инновационного развития «Приднепровье»», который может стать «фабрикой мысли» о путях и средствах перезагрузки отношений между акторами региональной инновационной экосистемы и неоиндустриального возрождения Приднепровья. With the signing of the Association Agreement bet¬ween Ukraine and the EU, the amendment of the Constitution of Ukraine regarding the implementation of Ukraine’s strategic course towards gaining full membership in the EU, approvement the National Security Strategy of Ukraine, in which European integration is recognized as the main direction of development of the Ukrainian state, Ukraine made the civilisational choice. The implementation of this civilizational choice obliges Ukraine to follow the path of the implementation of European integration reforms, to adopt the rules, norms and practices of the EU for successful integration into the European space and the system of formal institutions of the EU. This, among other things, concerns the need to implement the European approach to territorial division and regional policy, the introduce the smart specialisation approach into the system of strategic planning for regional development. The development of regional innovation ecosystems and the building of effective relationships between all their actors play a decisive role in the successful implementation of smart specialisation strategies.
The system of interrelationships between the actors of the regional innovation ecosystem of the Prydniprovskyi economic area is analysed for their presence and intensity in comparison with other regions and Ukraine as a whole. It has been determined that both national and regional innovation ecosystems of Ukraine (including the Prydniprovskyi economic area) lack effective relationships between their key actors.
The scientific and institutional provisions and recommendations for the formation of regional innovation ecosystems at the level of economic regions of Ukraine that meet the requirements of the European classification NUTS 1, in the context of the implementation of the Association Agreement between Ukraine and the EU and the smart specialisation approach, have been substantiated. They are the following: to empower of Regional Scientific Centers of NAS of Ukraine and MES of Ukraine with additional powers to coordinate relations between actors of regional innovation ecosystems within the areas of their action, as well as to amend and supplement of the Law of Ukraine «On Scientific and Scientific and Technology Activities» to expand the functions and powers of Regional Scientific Centers, turning them into effective interregional focal points for innovative development.
An approach to the formation of the Podillya regional innovation ecosystem within the Podillya economic area has been proposed. On the basis of the Prydniprovskyi Scientific Center of NAS of Ukraine and MES of Ukraine, it has been proposed to implement several experiments, firstly, on the formation of the Prydniprovskyi regional innovation ecosystem; secondly, on the creation of interregional public union «Platform for innovative development «Pridneprovie»», which can become a «factory of thought» on ways and means of restarting relations between actors of the regional innovation ecosystem and neo-industrial revival of the Prydniprovskyi economic area.